204. THE TUMOUR IMMUNE MICROENVIRONMENT IN OESOPHAGEAL ADENOCARCINOMA HAS PROGNOSTIC SIGNIFICANCE. (24th September 2022) - Lonie, James; Brosda, Sandra; Aoude, Lauren; Bonazzi, Vanessa; Patel, Kalpana; Lampe, Guy; Koufariotis, Lambros; Addala, Venkateswar; Wood, Scott; Thomas, Janine; Walpole, Euan; Mai, Tao; et al.
Abstract: Oesophageal adenocarcinoma (OAC) is a deadly disease with an increasing incidence globally. Treatment outcomes with traditional therapy have largely plateaued and responses to immunotherapy are modest at best, necessitating the need for better biomarker driven selection. We aimed to unravel the tumour neoantigen landscape and immune microenvironment in OAC patients to aid improved patient selection and inform novel immunotherapy trials. To characterise the tumour immune microenvironment and neoantigen landscape of OACs, we performed DNA sequencing (n = 117) and RNA sequencing (n = 115) on biopsies taken at pre-treatment endoscopy. Using expression-based computational methods we analysed transcriptomic data to profile infiltration levels of 28 immune cell populations and their functional orientation, as well as stromal signatures and immune checkpoint molecules. TCGA data was used for as a validation cohort. Tumour neoantigens were predicted using the pVAC-Seq pipeline. Using an immune based classification based on the tumour microenvironment composition, we identified three distinct phenotypes; immune-enriched (IE), heterogeneously-infiltrated (HI), and immune-cold (IC). The IE group showed improved survival compared to both HI and IC, with HI showing the worst survival. The HI-group showed no difference in stromal scores to the IE group, but showed significantly decreased adaptive-immune cell infiltration, indicating that an immunosuppressive stromal compartment may be driving outcomes for these patients. No difference was seen in total or quality neoantigen load between groups, but high correlation with antigen processing machinery is seen. Our analysis expands the knowledge of the relatively unknown tumour immune microenvironment of OAC. We have identified three immune TME-phenotypes with prognostic utility with current standard of care therapies; which may also act as potential immunotherapy biomarkers. This is being explored further in ongoing immune microenvironment research and will guide future translational studies.